Extracellular vesicles as a platform for membrane-associated therapeutic protein delivery. Issue 1 (1st January 2018) - Yang, Yoosoo; Hong, Yeonsun; Cho, Eunji; Kim, Gi Beom; Kim, In-San
ABSTRACT: Membrane proteins are of great research interest, particularly because they are rich in targets for therapeutic application. The suitability of various membrane proteins as targets for therapeutic formulations, such as drugs or antibodies, has been studied in preclinical and clinical studies. For therapeutic application, however, a protein must be expressed and purified in as close to its native conformation as possible. This has proven difficult for membrane proteins, as their native conformation requires the association with an appropriate cellular membrane. One solution to this problem is to use extracellular vesicles as a display platform. Exosomes and microvesicles are membranous extracellular vesicles that are released from most cells. Their membranes may provide a favourable microenvironment for membrane proteins to take on their proper conformation, activity, and membrane distribution; moreover, membrane proteins can cluster into microdomains on the surface of extracellular vesicles following their biogenesis. In this review, we survey the state-of-the-art of extracellular vesicle (exosome and small-sized microvesicle)-based therapeutics, evaluate the current biological understanding of these formulations, and forecast the technical advances that will be needed to continue driving the development of membrane protein therapeutics.